2022
DOI: 10.1101/2022.11.07.515520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bursting Translation on Single mRNAs in Live Cells

Abstract: Stochasticity has emerged as a mechanism to control gene expression. Much of this so-called "noise" has been attributed to bursting transcription. However, the stochasticity of translation has not similarly been investigated due to a lack of enabling imaging technologies. We developed techniques to track single mRNAs and their translation in live cells for hours, allowing measurement of previously uncharacterized translation dynamics. We applied genetic and pharmacological perturbations to control translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…We anticipate that similar results would be obtained with 5′TOP sequences derived from ribosomal protein mRNAs other than RPL32, although the magnitude of the difference in translational repression could be different if compared to another non-5′TOP transcript. In addition, the continued development of methodologies for imaging translation of single mRNAs for extended time periods and the interplay of translation with mRNA decay will enable the dynamics of mTOR regulation to be quantified in greater detail ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that similar results would be obtained with 5′TOP sequences derived from ribosomal protein mRNAs other than RPL32, although the magnitude of the difference in translational repression could be different if compared to another non-5′TOP transcript. In addition, the continued development of methodologies for imaging translation of single mRNAs for extended time periods and the interplay of translation with mRNA decay will enable the dynamics of mTOR regulation to be quantified in greater detail ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…SunTag and CRISPR-Sunspot have been developed as a means of visualizing the translation process, and SunTag in particular has been widely used from budding yeast to animal cells. 58,85,86 The application of such techniques to A. oryzae will help to elucidate the molecular mechanisms involved in the subcellular localization and translation of secretory enzyme mRNAs. In addition, analysis of the translational dynamics of secretory enzyme mRNAs in relation to SGs and PBs is expected to shed light on the translational regulation of secretory enzyme mRNAs by SGs and PBs.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of intracellular mRNA levels of target genes by the introduction of the MS2 system has been reported previously and has been analyzed to the extent that the localization of target mRNAs is not affected. [55][56][57][58]…”
Section: Visualization Of Glaa Mrna By Ms2 Systemmentioning
confidence: 99%
“…Eventually, Caf20 may regulate the efficiency of ribosome recruitment, that is, the rate of translation initiation, through a cycle of exchange between eIF4G and Caf20 in the 80S under rapamycin treatment (Figure 5). Recently, it has been reported that mTORC1 adjusts translation bursting (the frequency of translational active state) by phosphorylating 4E‐BP (Livingston et al, 2023). This supports our model that transient binding of the yeast 4E‐BP modulates translational efficiency in accordance with TORC1 activity.…”
Section: Discussionmentioning
confidence: 99%